Bibliometric analysis of global research hotspots in ovarian cancer immunotherapy from 2014 to 2024 using CiteSpace - Zhuo Zhang; Datian Fu; Yingdong Cao (Human Vaccines & Immunotherapeutics)
Bibliometric analysis has been employed to systematically evaluate the research landscape and emerging trends in ovarian cancer immunotherapy over the past decade (2014–2024). A bibliometric analysis of 3,100 publications (including reviews articles and articles) on immunotherapeutic interventions for ovarian malignancies was conducted using the Web of Science Core Collection (2014–2024). Temporal publication trends, institutional collaboration networks, and emerging research foci were systematically examined via CiteSpace software. A total of 3381 articles on ovarian cancer immunotherapy were initially identified, with 3100 records meeting the inclusion criteria for final analysis. The United States (n = 1,076) to become the major contributors of this field, with the University of Texas System (n = 131) being the most prolific institution. Among individual researchers, Odunsi, Kunle (n = 32) were the most extensively published authors. The most frequently cited reference was Matulonis UA (2019), with 235 citations. Co-citation cluster analysis revealed seven major research themes: expression, parp inhibitors, cancer immunotherapy, endometrial cancer, ovarian cancer, tumor associated antigens, chimeric antigen receptor. Parp inhibitors, tumor-associated antigens, and CAR-based therapies constituting critical themes for ovarian cancer research. Keyword burst detection identified emerging foci: dendritic cell, adoptive cell transfer, and regulatory T cell. These approaches offer promise for countering the TME characteristic of ovarian cancer, thereby enabling enhanced therapeutic efficacy. Prominent universities and developed nations form the finest alliances for research on immunotherapy for ovarian cancer. Three core research clusters are identified: dendritic cell-based therapies, adoptive immunotherapy, and tumor-infiltrating lymphocyte applications. These findings delineate the field’s evolving trajectory and offer strategic directions for future investigations, emphasizing translational potential and multidisciplinary integration.